Validation of Amblopusa vancouverensis (Coleoptera, Staphylinidae, Aleocharinae) - Yoo, In-Seong; Ahn, Kee-Jeong (Zootaxa, 2020)
In a recent publication (Yoo & Ahn, 2020), a holotype depository was not clearly indicated for the new species, Amblopusa vancouverensis Yoo & Ahn, 2020. In this paper we provide the missing type depository with a diagnosis of Amblopusa vancouverensis sp. nov. in order to validate the name under the conditions required by the ICZN (1999: Article 16.4.2).